High Expression of RAI14 in Triple-Negative Breast Cancer Participates in Immune Recruitment and Implies Poor Prognosis Through Bioinformatics Analyses - Cui, Ranliang; Zhao, Ting; Bai, Changsen; Ji, Ning; Hua, Jialei; Ren, Li; Li, Yueguo (Frontiers in Pharmacology, 2022)
Objective: The aim of present study is to explore the role of retinoic acid-induced protein 14 (RAI14) as a reciprocal protein of carboxypeptidase N1 (CPN1), and as a biomarker for prognosis and immunoregulatory effects in breast cancers. Methods:Interacting proteins of CPN1 were characterized by co-immunoprecipitation (CO-IP) and mass spectrometry. RAI14 expression was analyzed via Tumor Immune Estimation Resource (TIMER), the Human Protein Atlas (HPA), and the Gene Expression Proﬁling Interaction Analysis (GEPIA) databases. RAI14-related clinical prognosis was determined by the Kaplan-Meier plotter, the UALCAN, and the Breast Cancer Gene-Expression Miner (BC-GenExMiner) databases. The expression correlations between RAI14 and immune inﬁltration gene markers were analyzed using TIMER and were veriﬁed by immunohistochemistry and cytology experiments. Results: RAI14 is an interacting protein of CPN1. Higher RAI14 expression in triple-negative breast cancer (TNBC) was signiﬁcantly associated with poor prognosis in TNBC specially (RFS: HR=1.32, p=0.015). Molecular subclass, including estrogen receptor (ER), progesterone, and P53 status, as well as histological types, staging, menopause status, age, and triple-negative status, were observed corelated with RAI14 expression. Moreover, the expression of RAI14 was positively correlated with the expression of CD163 and PD-1, indicating the expression of RAI14 was corelated with exhaustion inﬁltration of M2 macrophages and T cell in TNBC. Furthermore, CPN1 overexpression was accompanied by RAI14 and PD-L1 upregulation, and a correlation was found among RAI14, CPN1 and PD-L1. Conclusions: RAI14 is a potential downstream molecule of CPN1, which may serve as a candidate prognostic biomarker for determining prognosis associated with immune inﬁltration in TNBC.